In Search of Identity: Apollonius Versus Julian—Representation on an Oil Lamp from the Belgrade City Museum - Tešić Radovanović, Danijela T. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The subject of the paper is a depiction of a bearded man on an ancient North African oil lamp from the 5th century, housed in the Belgrade City Museum (Antique Archaeology Collection). The bearded man is depicted with a laurel wreath in his hair. Based on earlier interpretations, it has been assumed that this figure might represent Christ, or rather Emperor Julian the Apostate (361–363). In previous research, the author proposed the thesis that the depicted figure should be identified as the philosopher Apollonius of Tyana, a claim examined in depth in the present paper. The article provides a comparative analysis of known and confirmed representations of Apollonius of Tyana and Julian the Apostate. Of particular importance is the latest research on Julian’s portraits, as well as textual sources that confirm the relevance of Apollonius of Tyana in Roman North Africa.
Keywords: North African oil lamps; Apollonius of Tyana; Julian the Apostate; iconography; Late Antiquity